Physical training in adults with asthma: An integrative approach on strategies, mechanisms, and benefits - de Lima, Fabiano Francisco; Pinheiro, David Halen Araújo; Carvalho, Celso Ricardo Fernandes de (Frontiers in Rehabilitation Sciences, 2023)
Asthma is a chronic airway disease characterized by airflow limitation and respiratory symptoms associated with chronic airway and systemic inflammation, bronchial hyperreactivity (BHR), and exercise-induced bronchoconstriction (EIB). Asthma is a heterogeneous disease classified according to distinct airway and systemic inflammation. Patients commonly present with several comorbidities, including anxiety, depression, poor sleep quality, and reduced physical activity levels. Individuals with moderate to severe asthma often have more symptoms and difficulty achieving adequate clinical control, which is associated with poor quality of life, despite proper pharmacological treatment. Physical training has been proposed as an adjunctive therapy for asthma. Initially, it was suggested that the effect of physical training might be attributed to the improved oxidative capacity and reduced production of exercise metabolites. However, in the last decade, there has been evidence that aerobic physical training promotes anti-inflammatory effects in asthma patients. Physical training improves BHR and EIB, asthma symptoms, clinical control, anxiety, and depression levels, sleep quality, lung function, exercise capacity, and dyspnea perception. Furthermore, physical training reduces medication consumption. The most commonly used exercise strategies are moderate aerobic and breathing exercises; however, other techniques, such as high-intensity interval training, have shown promising effects. In the present study, we reviewed the strategies and beneficial effects of exercise on clinical and pathophysiological asthma outcomes.